2011
DOI: 10.1002/jso.21776
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the growth factors and angiogenesis pathways: Small molecules in solid tumors

Abstract: Research over the last decades has provided us with a better understanding of the biology of solid tumors. In some solid tumor malignancies single molecular events leading to malignant transformation have been identified, whilst in others multiple pathways seem to play a role simultaneously. The delineation of such pathways has led to the identification of therapeutic targets. Multiple compounds are available now to treat those molecular aberrations. With the wider use of newer biologic therapies, the understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 161 publications
(191 reference statements)
0
12
0
2
Order By: Relevance
“…Anti-angiogenic drugs such as anti-VEGF antibodies (Bevacizumab) and tyrosine kinase inhibitors (Sorafenib, Sunitinib, Pazopanib, …) have proven some efficacy in the treatment of several metastatic cancers [14, 15]. Since their beneficial effect is only observed in association with chemotherapy, their true mechanism of action in the patients is still a matter of debate [1618].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-angiogenic drugs such as anti-VEGF antibodies (Bevacizumab) and tyrosine kinase inhibitors (Sorafenib, Sunitinib, Pazopanib, …) have proven some efficacy in the treatment of several metastatic cancers [14, 15]. Since their beneficial effect is only observed in association with chemotherapy, their true mechanism of action in the patients is still a matter of debate [1618].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, anti-angiogenic therapy emerges as an essential strategy for the treatment of cancer [3]. However, angiogenesis is a complex process mediated by multiple factors (e.g., hypoxia, growth factors, cytokines and oxidative stress [30]) and thus it is essential to decipher the critical steps involved in this process in prostate cancer. We believe that our studies had identify new players in this process and thus open new opportunities for therapy development for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…3 Some studies have shown that tumor angiogenesis occurs at the early stage of tumor formation, which plays a vital role in promoting progressive tumor growth. [4][5][6] Any tumor, including HCC, depends on the formation of a vascular network to provide its with oxygen and essential nutrients. 5,6 The tumor that has not acquired its own new blood supply can not grow to more than a few millimeters in size.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Any tumor, including HCC, depends on the formation of a vascular network to provide its with oxygen and essential nutrients. 5,6 The tumor that has not acquired its own new blood supply can not grow to more than a few millimeters in size. 4 Recent studies have demonstrated that angiotensin-converting enzyme (ACE), the regulator of the renin-angiotensin system (RAS), is overexpressed in several cancers including HCC, and directly involved in the process of cancer cell proliferation, differentiation, apoptosis, and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%